2018
DOI: 10.26603/ijspt20180501
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Glenohumeral Joint Rotational Range of Motion in Elite Tennis Players

Abstract: Background: Due to the repetitive overhead activity involved in playing tennis and the physical demands of the game, shoulder joint injury is common. There is limited research available describing sport specific risk factors for injury in tennis, however, changes in shoulder rotational range of motion (ROM) have been associated with injury in other overhead 'throwing' type sports.Purpose: This study had two purposes: i) to identify reference values for passive glenohumeral joint rotational ROM in elite tennis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Colour intensity and the form of the circle are proportional to the correlation coefficients. a dominant to non-dominant difference; b clinical relevance of a GIRD; *correlation is significant at the .05 level; ** correlation is significant at the .01 level performance instead of being a risk factor for injuries [33]. Manske et al [12] stated that a GIRD may be required to generate sufficient forces during tennis serves and does not lead to a pathological GIRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colour intensity and the form of the circle are proportional to the correlation coefficients. a dominant to non-dominant difference; b clinical relevance of a GIRD; *correlation is significant at the .05 level; ** correlation is significant at the .01 level performance instead of being a risk factor for injuries [33]. Manske et al [12] stated that a GIRD may be required to generate sufficient forces during tennis serves and does not lead to a pathological GIRD.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear whether physiological shoulder adaptations in overhead athletes are protective against tissue damage or if previous tissue damage leads to future shoulder injuries [ 20 ]. There is, furthermore, a debate whether physiological GIRD may even improves athletes’ performance instead of being a risk factor for injuries [ 33 ]. Manske et al [ 12 ] stated that a GIRD may be required to generate sufficient forces during tennis serves and does not lead to a pathological GIRD.…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible that the repetitive movements needed to drive the forklift truck caused these differences in the spinal ROM between groups. Previous studies described ROM adaptations in other joints due to repetitive movements, as shown in the shoulder rotation of tennis, baseball, and softball players [ 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kramárová et al suggested that decreased ROM and musculoskeletal discomfort are symptoms of the beginning of MSDs for forklift operators [ 8 ]. Past studies observed how repeated and specific movements could generate adaptations in a joint’s ROM [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Previous studies have demonstrated tennis players similarly display rotational ROM adaptations of the dominant shoulder. [21][22][23][24] However, HRV data pertaining to tennis players are scarce, further limiting our understanding of its implications on shoulder ROM adaptations.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%